Investigating The Accumulation of Aflatoxin in The Serum of School Students - Al-Dulaimi , Fahad K.Y.; Al-Tarjuman , Janan K.; Mustafa , Mustafa M. (American Journal of Botany and Bioengineering, 2026)
Mycotoxins are among the most important biological contaminants in food. Aflatoxins are considered the most dangerous due to their ability to accumulate in liver tissue and blood, and their carcinogenic and immunosuppressive effects. This study aimed to investigate the accumulation of aflatoxins in the blood serum of primary school students in Al-Sharqat City who regularly consume potato and corn chips. Blood samples were taken from 60 students and analyzed using an ELISA test to detect total aflatoxins, in addition to dietary data collected through a questionnaire. The results showed that 58.3% of the students regularly consume potato chips and the average aflatoxin concentration among regular consumers was 1.4 ng/ml, exceeding the internationally accepted limit 1 ng/ml. Furthermore, children who consume both potato and corn chips had the highest recorded concentrations 1.7 ng/ml. These results indicate a clear link between potato chip consumption and aflatoxin accumulation in the blood, reflecting the potential for contamination of these foods due to improper storage. This underscores the need for regular monitoring of popular food products and increased consumer awareness of their health risks.